Church Music as a Media for Proclaiming the Gospel and Discipleship in the Digital Ecosystem: A Contextual Theological Perspective - Samuel Elkana; Henry Sutanto; Donalia Reynaldo (International Forum of Researchers and Lecturers, 2025)
This study examines the role of digital church music as a medium for evangelism and discipleship within the digital ecosystem. It employs a mixed methods approach using a sequential explanatory design, in which quantitative data collection is followed by qualitative exploration. Quantitative data were gathered through an online survey of at least 200 respondents to measure the intensity of digital worship music consumption, perceived gospel understanding, faith reflection, and spiritual engagement. Qualitative data were obtained through in-depth interviews with 15–20 key informants and digital content analysis of worship songs, service videos, and social media interactions. The findings indicate that digital church music contributes to strengthening gospel understanding, encouraging faith reflection, and expanding discipleship practices through online spaces. A moderate positive correlation between music consumption intensity and spiritual engagement suggests that music functions as a contextual medium for faith formation. This study highlights the importance of adaptive theological and pastoral strategies for church music ministry in the digital era.